The Correlation Between Energy Carriers in the Blood Plasma of Early Lactating Dairy Cows Receiving Supplemental Choline - M. G. Rahmani; R. G. Kamalyan; M. J. Dehghan-Banadaky; G. J. Eskandari (ՀՀ ԳԱԱ հրատ.)
In an experiment on early lactating Holstein cows it was shown the presence of correlation between non-esterified fatty acids (NEFA), β-hydroxyl butyric acid (BHBA), triglyceride (TG) and glucose in plasma while feeding diet with choline. TG had a positive correlation with glucose. Հոլսթեյն ցեղի կովերի կաթնատվության վաղ շրջանում կերի հետ խոլինի կերակրման պայմաններում գրանցվում է հավաստի կորելյացիա արյան պլազմայի չեթերիկացված ճարպաթթուների, β-հիդրօքսիկարագաթթվի, եռացիլգլիցերիդների և գլյուկոզի միջև։ Եռացիլգլիցերիդների և գլյուկոզի միջև դիտվում է դրական կորելյացիա։ В опытах коровах породы Голштейн показано наличие корреляции в плазме крови между неэстерифицированными жирными кислотами (НЖК), β-гидроксибутиратом, триглицеридами (ТГ) и глюкозой в ранний период лактации при скармливании холина. ТГ имели положительную корреляцию с глюкозой.
Keywords: Electrolytes